2011
DOI: 10.1016/j.whi.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Violence Prevention among HIV-Positive Women with Histories of Violence: Healing Women in Their Communities

Abstract: a b s t r a c tExperiences of past and current gender-based violence are common among HIV-positive women in the United States, who are predominantly from ethnic minority groups. However, culturally congruent, feasible interventions for HIVpositive women who have experienced past and/or current violence are not widely available. The Office on Women's Health Gender Forum has made several recommendations for responding to the National HIV/AIDS Strategy Implementation Plan, including recommendations to incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Yet, despite calls for violence screening and intervention within HIV care and treatment programs, few HIV clinics have IPV-specific protocols in place [98]. HIV care and treatment programmes can draw upon existing guidelines for screening and responding to IPV in the health sector [91,99], or can look to a growing number of specialist programmes that address IPV alongside HIV [100][101][102][103]. To ensure that women benefit from medical advances, future studies should develop and test interventions to address IPV within HIV clinical care.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, despite calls for violence screening and intervention within HIV care and treatment programs, few HIV clinics have IPV-specific protocols in place [98]. HIV care and treatment programmes can draw upon existing guidelines for screening and responding to IPV in the health sector [91,99], or can look to a growing number of specialist programmes that address IPV alongside HIV [100][101][102][103]. To ensure that women benefit from medical advances, future studies should develop and test interventions to address IPV within HIV clinical care.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analytic reviews and recent studies suggest that trauma-focused interventions that address SUDs, GBV (including CSA), PTSD associated with GBV-related trauma, and HIV/AIDS in an integrated, concurrent approach are more likely to succeed, to be more cost-effective, to increase medication adherence and to reduce symptoms of PTSD 57,58 and are more sensitive to client needs than parallel or sequential interventions. 57,59,60 Seeking Safety is the most widely tested trauma-focused integrated treatment to-date (20 RCTs and pilot studies) and has been found to significantly reduce substance use and PTSD symptoms across different populations.…”
Section: Resultsmentioning
confidence: 99%
“…57,59,60 Seeking Safety is the most widely tested trauma-focused integrated treatment to-date (20 RCTs and pilot studies) and has been found to significantly reduce substance use and PTSD symptoms across different populations. 60,61 One study of Seeking Safety also demonstrated significant reduction in unprotected sex.…”
Section: Resultsmentioning
confidence: 99%
“…Participants in a 2010 forum sponsored by the U.S. Office on Women's Health and the Joint United Nations Programme on HIV/AIDS identified practical opportunities to integrate services for HIV and gender-based violence and described this integration as fundamental to achieving and building on the goals of the National HIV/AIDS Strategy (Forbes, Bowers, Langhorne, Yakovchenko, & Taylor, 2011;Wyatt et al, 2011). In 2013, a presidential working group that was convened to address the intersection of violence and HIV among women found that childhood and adult trauma are key drivers of HIV infection and poor health outcomes among women living with HIV, and called for organizations to "develop, implement, and evaluate models that integrate trauma-informed care into services for women living with HIV" (White House Interagency Federal Working Group, 2013).…”
Section: The Link Between Trauma and Poor Healthmentioning
confidence: 99%